Youth-centred research to help prevent and mitigate the adverse health and social impacts of pregnancy amongst young Papua New Guineans. Issue 54 (8th November 2018) - Bell, Stephen; Kennedy, Elissa; Black, Kirsten; Vallely, Andrew; Vallely, Lisa; Mola, Glen; Kaldor, John; Bagita, Mary; Ninnes, Caroline; Pomat, William; Kelly-Hanku, Angela
Abstract: Despite persistent international attention, adolescent pregnancy remains a major public health concern in low- and middle-income countries, like Papua New Guinea (PNG), where health inequities related to social and cultural norms, gender power imbalance, education and socio-economic deprivation affect young and unmarried women in particular. In PNG – where there is high adolescent fertility, high early childbearing and high maternal mortality ratio, and evidence of high rates of unintended pregnancy and abortion among young women – adolescent pregnancy is a policy priority. Yet there are no youth-specific sexual, reproductive and maternal health services or community-based outreach programmes. There is limited in-depth qualitative data on young women's and young men's experiences of pregnancy, the social contexts within which these pregnancies occur, young people's contraception practices and experiences with existing sexual, reproductive and maternal health services. These issues inhibit the design and delivery of youth-friendly health services and outreach support programmes that could prevent or mitigate adverse health and social outcomes associated with adolescent pregnancy. In this commentary article, we propose the need for novel youth-centred research to inform the development of policies, health services and outreach programmes that pay honest and respectful attention to young people's lived experiences of pregnancy. Whilst we focus on the situation in PNG, these ideas are relevant to diverse low resource settings where the harmful impacts of health inequities among young people persist and are particularly detrimental.